2011
DOI: 10.1007/s12282-011-0277-2
|View full text |Cite
|
Sign up to set email alerts
|

Can patients with metastatic breast cancer be cured after introduction of newer and more effective agents?

Abstract: Unlike early stage breast cancer, metastatic breast cancer (MBC) is generally considered incurable except for a small number of patients with oligometastatic disease. The goal of treatment of MBC should be the prolongation of life and improvement of symptoms and quality of life. The prognoses of patients with MBC, however, have been improved with the introduction of newer, more effective agents. Therefore, the clinical question arises whether MBC patients can be cured with these new therapeutic agents. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…[1] For this purpose in metastatic breast cancer patients starting appropriate CT in an early period and continue to be an appropriate time prolong the PFS and OS and increase the quality of life. [39,40] In both univariate and multivariate analysis, we found that, among the patients with brain metastasis, the number of patients who received CT after the development of the first metastasis in any organ was very low. It may have resulted from the administration of HT instead of CT to the metastatic patients, especially due to advanced age and impaired general health.…”
Section: Discussionmentioning
confidence: 93%
“…[1] For this purpose in metastatic breast cancer patients starting appropriate CT in an early period and continue to be an appropriate time prolong the PFS and OS and increase the quality of life. [39,40] In both univariate and multivariate analysis, we found that, among the patients with brain metastasis, the number of patients who received CT after the development of the first metastasis in any organ was very low. It may have resulted from the administration of HT instead of CT to the metastatic patients, especially due to advanced age and impaired general health.…”
Section: Discussionmentioning
confidence: 93%
“…Two articles use cure in reference to chronic myeloid leukemia, 1 referring to a “functional” cure, where indefinite tyrosine kinase inhibitor use prevents disease progression, 10 and the other referring to “therapy discontinuation without molecular response.” 9 Four articles were paired in a single theme issue of the journal Breast Cancer and discussed the possibility for a cure in metastatic breast cancer. 17 20…”
Section: Resultsmentioning
confidence: 99%
“…9 Four articles were paired in a single theme issue of the journal Breast Cancer and discussed the possibility for a cure in metastatic breast cancer. [17][18][19][20] Several articles use the word cure in the context of cure function analyses which proves mathematically that some surviving subset experiences mortality comparable to matched normal controls. 25,29 A single article used the term to describe the outcome of 1 patient who used sorafenib in the neoadjuvant setting to allow an initially unresectable hepatocellular carcinoma to become resectable, thus serving as a bridge to transplant.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the impact on survival of detecting an oligometastatic disease is still unknown [49], [50] and, hopefully, the utility of an early detection of metastatic disease suitable of cure with the ongoing molecular targeted agents or novel therapeutics drugs [51].…”
Section: Discussionmentioning
confidence: 99%